Finance and Development, December 1978. (Finance and Development; Finance and Development, 1978)
This paper highlights that the 1978 World Bank Annual Meeting, held in Washington, D.C. during September 25-28, 1978, emphasized that greater efforts need to be made by both developed and developing countries, on domestic as well as international fronts, to stimulate lagging growth and to improve the well-being of the poorest. Just as developing countries agreed that economic takeoff was based as much on their own internal policies as on the external environment, the industrialized nations acknowledged that their own economic well-being was more closely linked to the growth of the Third World.